The biomechanics of rowing - Kleshnev, V. (The Crowood Press Ltd., 2016)
In rowing, races are often won in spite of, not because of, technique and many misconceptions still preoccupy both rowers and coaches. This book explains the facts about rowing technique and will help you to find the right way to achieve your best performance. The Biomechanics of Rowing offers a unique insight into the technical and tactical aspects of rowing, based on over twenty-five years experience of working with the best rowers and coaches all round the globe, a careful analysis of millions of data samples, and comprehensive biomechanical modelling with the aim of finding an optimal balance of variables.